(untitled) (Annals of Medical Research, 2023)
Aim: The present study aimed to investigate the possible hepatoprotective effect pycnogenol (PYC) in gentamicin (GEN)-induced liver injury in rats. Materials and Methods: The study consisted of four groups of seven rats; control, PYC (20 mg/kg for 8 days), GEN (80 mg/kg for 8 days) and GEN+PYC. At the end of the experiment, liver tissues of all groups were collected for histopathological and immunohistochemical (fibrillin-1, caspase-3, and betatrophin antibodies) evaluation. Results: Histopathological analysis revealed that the GEN treated group had liver damage as a result of the GEN administration compared to the control group. Additionally, fibrillin-1, caspase-3, and betatrophin expression all increased in rat liver tissues. However, PYC pretreatment significantly reduced the expression of the aforementioned antibodies and mitigated liver damage. Conclusion: The anti-apoptotic and antioxidant properties of PYC may help to preserve liver histoarchitecture against GEN-induced hepatotoxicity.